Model Matematika Untuk Kontrol Campak Menggunakan Vaksinasi - Ulfa, Maesaroh; Sugiyanto, Mr. (Jurnal Fourier, 2013)
Measles (also known as Rubeola, measles 9 day) is a highly contagious virus infection, characterized by fever, cough, conjunctiva (inflammation of the tissue lining of the eye) and skin rash. The disease is caused by infection of measles virus paramyxovirus cluster. It is a deadly disease. Vaccination is the most effective strategy to prevent the disease. It is generally given to children. This research aims to establish a model of the effect of measles vaccination, forming the point of equilibrium and analyze the stability, create a simulation model and interpret them, and to know the design to optimize the vaccination coverage required, so it can reduce the spread of this disease. This research was conducted by the method of literature study. It is expected to provide an overview of the mathematical model used to control measles vaccination with division of classes SEIR. The steps taken is identifying the problem, formulating assumptions to simplifying the model, making the transfer diagram, defining parameters, determining the equilibrium points and analyzing the stability, simulating the model, and forming the design to optimize the vaccination. Then from this research can be obtained free balance point of endemic and diseases and their stability. Based on the results obtained, the simulation is done by taking the data in Yogyakarta, and obtained vaccination coverage with two doses that can increase the herd immunity with lower vaccination coverage.